A Case of Acute Disseminated Encephalomyelitis in a Middle-Aged Adult. (9th June 2015) - Mahdi, Nicole; Abdelmalik, Peter A.; Curtis, Mark; Bar, Barak
Abstract : Objectives . Acute disseminated encephalomyelitis (ADEM) is an inflammatory demyelinating disorder that is often preceded by infection or recent vaccination. Encephalopathy and focal neurological deficits are usually manifest several weeks after a prodromal illness with rapidly progressive neurologic decline. ADEM is most commonly seen in children and young adults, in which prognosis is favorable, but very few cases have been reported of older adults with ADEM and thus their clinical course is unknown. Methods . Here we present a case of ADEM in a middle-aged adult that recovered well after treatment. Results . A 62-year-old man presented with encephalopathy and rapid neurological decline following a gastrointestinal illness. A brain MRI revealed extensive supratentorial white matter hyperintensities consistent with ADEM and thus he was started on high dose intravenous methylprednisolone. He underwent a brain biopsy showing widespread white matter inflammation secondary to demyelination. At discharge, his neurological exam had significantly improved with continued steroid treatment and four months later, he was able to perform his ADLs. Conclusions . This case of ADEM in a middle-aged adult represents an excellent response to high dose steroid treatment with a remarkable neurological recovery. Thus it behooves one to treat suspected cases of ADEM in an adult patient aggressively, as outcome can be favorable.